Proceso de atención de enfermería en paciente de 57 años con diagnóstico de tuberculosis intestinal y VIH. - Sánchez Rosero, Josselyn Maricela (2020)
Tuberculosis is an infectious disease, which is transmitted from one person to another through droplets that have been spread through the air by speaking, sneezing or coughing. The people most vulnerable to catching tuberculosis are immunosuppressed patients (HIV) because their defense system is weakened, this being one of the risk factors with the greatest probability of contagion. Intestinal tuberculosis is considered to be a rare disease because it is difficult to diagnose with certainty. It is the sixth most common form of intestinal tuberculosis and HIV, and some of its characteristic signs and symptoms are low weight and fever. Tuberculosis and HIV both diseases can trigger a number of affectation even death if not treated in time, the most common factors of this pathology are sex, socioeconomic status, population, and patients with pre-existing diseases. In the development of the clinical case, it was possible to evidence which are the altered functional patterns of the patient diagnosed with intestinal tuberculosis and HIV 10 years ago. This is done in the process of nursing care with the objective of fulfilling our interventions as future professionals and obtaining good results.